The Effectiveness of Therapy for Gender Equity Based on Religious Doctrines on Gender Role Schema and Psychological Capital in Girls to Delay Marriage Age - Mahsa Jorjorzadeh; Parvin Ehtesham Zadeh; Reza Pasha; Fatemeh Sadat Marashian (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2021)
Aim and Background: Increasing the age of marriage of young people, biological celibacy and the problems of late marriage, especially for girls, is an issue that must be addressed seriously. In particular, it creates a variety of psychological and social problems for single people. The aim of this study was to develop a gender justice training package based on religious teachings and its effectiveness on psychological capital and the gender role schema of girls with delayed marriage. Methods and Materials: The design consisted of two parts, qualitative and quantitative. In the qualitative part, the inference was analytical and in the quantitative part, it was experimental and pre-test-post-test with the control group. The statistical population included single girls (45-30 years old) referring to mental health centers in Tehran. Thirty people were selected as a sample by purposive sampling method and were randomly divided into two groups of 15 people (experimental and control groups). The members of the experimental group underwent a researcher-made training package on gender justice based on group religious teachings for 8 sessions. The control group did not receive any intervention. The research tools included the psychological capital questionnaire of Vetanz et al., Bam gender schemas. Research data were analyzed by multivariate analysis of covariance. Findings: Results: The results showed that gender justice education based on group religious teachings was effective in increasing psychological capital and improving the gender role schemas of girls with delayed marriage (p<.001). Conclusions: It seems that the need to apply gender justice based on religious teachings in order to improve the psychological capital and gender role schemas of girls with delayed marriage.